Prospects of a Shariah audit framework for Islamic financial institutions in Malaysia - Yussof, Sheila Ainon (International Institute of Advanced Islamic Studies (IAIS) Malaysia., 2013)

(untitled)
The need to be in conformity with religious and ethical principles, or to be Shariah compliant, is the unique and distinctive feature of Islamic finance which sets it apart from its conventional counterpart. Islamic financial institutions (IFIs) are to be audited not only on financial performances but also on their adherence to Shariah precepts, including broader ethical and moral parameters. Currently there is no proper framework to govern the practice of internal Shariah auditing in IFIs. The recently issued Central Bank of Malaysia’s Shariah Governance Framework (CBM-SGF) has made it compulsory for IFIs to perform a regular internal audit of transactions, operations and information systems particularly at the product implementation stage to ensure a comprehensive compliance with Shariah. This has posed a challenge to Islamic banks and Takaful companies, to develop their own internal Shariah audit architecture and to train a new breed of internal auditors in the science and ethics of Shariah audit based on generalised guidelines under the new directive. This paper highlights persistent problems relating to inadequate auditing at the business operations level and prevailing issues in Shariah audit. Recommendations are made for the industry to adopt a common internal Shariah audit framework as a move towards standardisation and uniformity of audit practice.